The cross-aisle seismic performance of storage rack base connections. (July 2016) - Petrone, F.; Higgins, P.S.; Bissonnette, N.P.; Kanvinde, A.M.
Abstract: Steel storage racks used in retail stores and warehouses are seismically designed as moment resisting frames in the down-aisle direction, and braced frames in the cross-aisle direction. While their down-aisle response is relatively well understood, there is little understanding of their cross-aisle response, especially as it pertains to the desired mode of inelastic deformation and associated design methods. Results are presented from six full scale tests on braced frames representing storage racks in the cross-aisle direction. These tests investigate the base plate thickness and dimensions, and the upright (column) cross section. The experiments indicate that inelastic deformation in the base plate provides stable hysteretic response with significant ductility and energy dissipation. Ductile tearing is also observed in welds connecting the base plate to the upright. However, it does not appear to negatively influence the hysteretic response. The tests are complemented by Finite Element (FE) simulations of the base connections. These simulations provide insights into internal force distributions within the connections. Based on these insights, analytical equations are proposed for characterizing the backbone curve of the hysteretic response, for use in displacement based design methods. It is determined that the current approach for characterizing design forces in the anchors is unconservative, since it does not incorporate the effects of strain hardening or the membrane action as the base plate undergoes large deformations. A new approach which incorporates these phenomena is presented, and determined to be significantly more accurate. Limitations of the study are outlined and directions for future work are identified. Highlights: Cross-aisle response of racks is not well understood. This response is controlled by the hysteretic behavior of base connections. Six tests and finite element models are conducted. Behavioral insights are generated about the response of these connections. Analytical models are presented to characterize their hysteretic response.